Reducing the Incidence of Mammals on Public Highways Using Chemical Repellent - Linas Balčiauskas; Marius Jasiulionis (The Baltic Journal of Road and Bridge Engineering)
In Lithuania, one of the measures to reduce the number of wildlife-vehicle accidents (WVA) is the fencing of highways. However, any gaps in the fencing have the potential to become an animal crossing site and consequently are likely to lead to increased WVA. Attempting to reduce the number of animals venturing onto roads, trials with the chemical repellent Wam Porocol® were conducted. This was the first such investigation in Lithuania. The effectiveness of Wam Porocol® was investigated over a six-month period in five gaps in the fencing, with five parallel control places without repellent also checked. In total, 11 mammal species (nine wild and two domestic) were registered, the most frequent of which were roe deer (32 cases), red foxes (18), raccoon dogs (16), red deer and martens (14 of each), plus domestic dogs (13 cases). Hoofed animals accounted for 42.1% of the total, with wild and domestic carnivores totalling 57%. It was found that, on average, every gap in the fencing allows the passage of 300–400 mammals onto the highway annually. Applying repellent, these numbers were reduced to 170–240 animals annually. Thus, the repellent Wam Porocol® reduced the number of mammals venturing onto highways by 42%. The daily average of gap-crossing mammal numbers was significantly lower (p < 0.025) using repellent than in control places.